Leaf anatomy and morphometry in three eucalypt clones treated with glyphosate - LD. Tuffi Santos; BF. Sant'Anna-Santos; RMSA. Meira; FA. Ferreira; RAS. Tiburcio; AFL. Machado (Brazilian Journal of Biology)
This work aimed to evaluate the effects of simulated drift of glyphosate on the morphoanatomy of three eucalypt clones and to correlate the intoxication symptoms on a microscopic scale with those observed in this visual analysis. The effects of glyphosate drift were proportional to the five doses tested, with Eucalyptus urophylla being more tolerant to the herbicide than E. grandis and urograndis hybrid. The symptoms of intoxication which were similar for the different clones at 7 and 15 days after application were characterized by leaf wilting, chlorosis and curling and, at the highest rates, by necrosis, leaf senescence and death. Anatomically glyphosate doses higher than 86.4 g.ha-1 caused cellular plasmolysis, hypertrophy and hyperplasia, formation of the cicatrization tissue and dead cells on the adaxial epidermis. The spongy parenchyma had a decrease, and the palisade parenchyma and leaf blade thickness had an increase. The increased thickness in leaf blade and palisade parenchyma may be related to the plant response to glyphosate action, as a form of recovering the photosynthetically active area reduced by necroses and leaf senescence caused by the herbicide.